El Plan de Atención Básica en los municipios descentralizados de Colombia, 2001-2003 (2004)
ABSTRACT: The Colombian Basic Health Care Plan (PAB) as a part of the General Social Security Health System (SGSSS) involves several activities addressed to the community in order to guarantee the conditions required in the avoidance of disease or death risk caused by biological, environmental and social factors, which may be prevented. The Ministry of Health issued regulation 4288 in 1996 and the PAB guidelines were established in 2000 as the plan assessment reference. This study was carried out with a randomized sample of 212 decentralized, categorized municipalities. The survey was completed by 174 municipalities from the study sample. The study allowed to identifying advantages and disadvantages, as well as the conclusion on the main problems found in the PAB management and the establishment of recommendations useful for decision making at a local level, contributing to improve the population.s public health. An unequal process of territory autonomy development in facing health and the lack of organization and management from the municipal and local health direction affected the development of the PAB. In addition, Colombians public health needs to highly exceed the actions implied in the plan. Therefore, it is necessary to re-evaluate it through strategies based on inter institutional and inter sectors work, facilitating favourable environments and strengthening community action to allow collective institutions to become the welfare support.